Listening as part of the teaching of simultaneous translation: how to program activities and put them into practice - Nina Koroleva (Ибероамериканские тетради)
This study proposes some ideas about simultaneous translation teaching from Spanish into Russian, using the texts and speeches video pronounced in Spanish language with all multimedia information pertaining to the speaker: ondemand video(s), the country statement, a summary of the statement, audio files.